Analisis Penilaian Kinerja Keuangan Perusahaan Manufaktur Sektor Consumer Good Dengan Pendekatan EVA (Economic Value Added) di Bursa Efek Indonesia Pada Tahun 2010 - 2013 - Saptono, Bayu; , Drs. Ma'ruf, M.M (2015)
Economic Value Added (EVA) is one of the performance measurement that takes into account precisely all the factors related to the creation of value (Value). This research is a descriptive study using secondary data. The population in this study are all consummer sector manufacturing companies that go public goods listed on the Stock Exchange. Samples taken are 3 consummer sector manufacturing companies that go public goods listed on the Stock Exchange. Methods of data analysis using financial performance analysis techniques with EVA method. The results showed that the Consumer Goods company has succeeded in creating additional value for investors and could increase the value of the company. Evident from the results of the analysis of financial performance with the approach of Economic Value Added (EVA), which derive value - average positive EVA.